Pengaruh Stres Kerja Terhadap Kepuasan Kerja Karyawan Selama Pandemi Di Pabrik Kue Nuni Cookies, Tangerang. - Yohana Claudya; Leo Alexander Tambunan (Jurnal Syntax Transformation, 2021)
This research was conducted to connect whether there is an effect of job stress (X) as an independent variable with indicators of workload (X1), leader attitude (X2), working time (X3), conflict (X4), communication (X5), and work authority (X6). on job satisfaction (Y) as the dependent variable. This study uses quantitative methods with data acquisition through the results of questionnaires distributed to 50 employees who work at the Pabrik Kue Nuni, Cookies, Tangerang during the pandemic. From the results of research that has been done, it is found that there is a significant effect of work stress on employee job satisfaction at the Pabrik Kue Nuni, Cookies, Tangerang